Chemical composition is of the leaf oil from Uvaria grandiflora Roxb. ex Hornem from Ha Tinh province - Dai, Do Ngoc; Thang, Tran Dinh; Hoi, Tran Minh; Dung, Nguyen Xuan (Academia Journal of Biology, 2012)
The leaf oil of Uvaria grandiflora Roxb. ex Hornem collected from Ha Tinh province, Vietnam, in May 2007 was isolated by steam distillation to give oil yield 0.1% and analyzed by Capillary GC and GC/MS. Thirty three components have been identified accounting more than 94.2% of the oil respectively. The major constituents of this oil appeared to be bicyclogermacrene (35.7%), β-caryophyllene (13.9%) and (Z)-b-ocimene (10.7%). Less predominant constituents included β-elemene (6.6%), germacrene D (6.0%), α-humulene (3.9%), bicycloelemene (2.5%), (E)-b-ocimene (2.3%), α-amorphene (1.8%), β-selinene (1.7%), and a-cubebene (1.0%). All the other components were in concentration of less than 0.1-0.9%.